Effects of bilingual teaching strategy on pupil’s achievement in mathematics in Oyo state primary schools (2013)
After a careful analytical observation, Primary Education which is the foundation upon which further education is built is considered not to be at its best presently in Nigeria. The mode of instruction used by teachers of Mathematics (being a core subject) seems to be contributory to the performance of pupils in primary schools. This study investigated the effect of Bilingual teaching Strategy on pupils’ achievement in Mathematics with the view to improving such. The research adopted the pre-test, post-test control group using 2×2 factorial matrix. The subjects consisted of 141 primary five pupils. Two local governments were randomly selected out of the four local governments in Oyo town. Each of the local government was clustered into two groups; two schools were randomly selected from the two groups and randomly assigned to treatment, making four schools. Four instruments, namely; Mathematics Achievement Test, Pupils Attitude Scale, Teacher Instructional Guide on Bilingual Teaching Strategy and Conventional Teaching Strategy, were used to collect data. Three hypotheses were tested and data were analyzed using descriptive statistics and Analysis of Covariance (ANCOVA). The result of the study showed that there was a significant effect of treatment (teaching strategies) on pupils’ achievement. [F (1,141) =185.372, P< 0.05]. Mean score of Bilingual teaching strategy is ( =13.67), and conventional group (control) scored the least ( =7.10) in achievement in Mathematics. It revealed no significant main effect of attitude [F (1, 141) =1.258, P>0.05]. Findings also imply that pupils’ attitude does not serve as hindrance to their achievement in Mathematics; among other discoveries. The work, therefore, recommends, inter-alia, that Mathematics teachers should utilize bilingual approach to support teaching of Mathematics in primary schools to enhance pupils’ performance.